Farmers' Perception on the Establishment of Knowledge Centres in Coastal and Tribal Areas of Gujarat - Mahalakshmi , P.; Gopal, C.; Muralidhar, M.; Kumar, Prem; Patil, P. K.; Kailasam, M.; Solanki , H. G.; Borichangar, R. V.; Vanza, J. G. (Indian Journal of Extension Education, 2017)
Astudy was undertaken in Gujarat to analyse the farmers' perception on the establishment of knowledge centres in coastal  and tribal areas. Among the various services, all the respondents needed details on the aquaculture practices, market  pricing, and e-mail/internet facilities in the centre for upgrading their knowledge in aquaculture and better  communication among the fellow farmers and experts respectively. Farmers strongly agreed that the knowledge centre is  necessary for coastal and tribal development. It is also essential for getting information quickly and useful for decision  making in culture practices. The sampled respondents ranked lack of unity among the village people as the major  challenge for implementation of the centre with a rank based quotient of 89.58 followed by the requirement of  sustainability in both content and finance (85.00) and interest in usage of advance technologies like computer, internet etc.  among the farmers (83.33). Adequate training to the farmers was suggested for better utilization of ICTtools. The training  in advanced technology helps the farmers to increase their efficiency and profitability of aquaculture production. Overall  opinion for the establishment of centre and the improvement of the initiatives are also discussed.
Keywords: ICT; knowledge centre; tribal farmers; Gujarat